TMS on Right Frontal Eye Fields Induces an Inflexible Focus of Attention. (9th October 2012) - Ronconi, Luca; Basso, Demis; Gori, Simone; Facoetti, Andrea
Abstract : The focus of spatial attention can be not only oriented to a particular location, but also adjusted in its size to select visual information from a narrow (zoom-in) or broad (zoom-out) region of the visual field. Attentional orienting, saccades programming, and visual search have been linked to the frontal eye fields (FEF) activity. However, the FEF causal role in the frontoparietal network for the attentional focus size modulation remains unclear. Here, we delivered single-pulse transcranial magnetic stimulation (TMS) on FEF while participants performed an attentional zooming task. They were asked to detect a visual target appearing at 3 eccentricities from the fixation. Two cue types modulated the size of the attended region: a small cue was employed to narrow the attentional focus, whereas a large cue induced participants to broaden the attended region. Results showed that TMS delivered on the right FEF, but not on the left FEF, was able to interfere with both zoom-in and zoom-out attentional mechanisms. Our results provide the first evidence of the right FEF casual role in the attentional zooming control and give new insights into the neural mechanisms of dysfunctional spatial attention deployment shown in neurodevelopmental disorders, such as autism and dyslexia.